(untitled) (Bangladesh Journal of Botany, 2021)
Estimation the magnitude of heterosis for yield and yield contributing parameters of Okra was conducted. Fifty-four F1 hybrids were generated by line x tester mating design. These F1s along with 21 parents and commercial check (Mhyco-10) were evaluated in a randomized block design with two replications. Analysis of variance with respect to yield and quality characters in parents and hybrids were highly significant. This indicates the existence of high variation in parents and hybrids for different characters studied. Out of 54 cross combinations, seven crosses revealed the significant and positive heterosis over better parent. While 11 crosses showed positive and significant heterosis over economic parent. It is pertinent to mention that the crop has potential to produce the heterotic cross combinations and such crosses can be used for further improvement of this crop. Five crosses, namely L43 × T44, L22 × T36, L22 × T44, L53 × T36 and L31 × T23 were found to be potential for the production of fruit yield per plant and other desired characters. The high heterosis and per se performance was found in hybrid L43 × T44 over both better parents and standard check for fruit yield per plant. This indicates that the cross can be exploited commercially. Bangladesh J. Bot. 50(3): 531-540, 2021 (September)